Exhibition as the Controlled Encounter of Two Countries: ”Poland – Czechoslovakia: Centuries of Neighborhood and Friendship” (1977–1978) - Petra Skarupsky (Miejsce)
The most complex official exhibition project organized between Poland and Czechoslovakia during the Cold War was a show titled ”Poland – Czechoslovakia: Centuries of Neighborhood and Friendship”. The show was conceived to celebrate the 30th anniversary of the first Czechoslovak – Polish Treaty of Friendship and Mutual Help. The project was co-organized by Czechoslovak and Polish institutions, and travelled to Kraków, Warsaw, Bratislava, and Prague for month-long presentations.